T regulatory cell-associated tolerance induction by high-dose immunoglobulins in an HLA-transgenic mouse model of pemphigus - Hudemann, Christoph; Hoffmann, Jochen; Schmidt, Enno; Hertl, Michael; Eming, Rüdiger (Cells, 2023)
Pemphigus vulgaris (PV) is a potentially lethal autoimmune bullous skin disorder caused by IgG autoantibodies against desmoglein 3 (Dsg3) and Dsg1. During the last three decades, high-dose intravenous immunoglobulins (IVIgs) have been applied as an effective and relatively safe treatment regime in severe, therapy-refractory PV. This prompted us to study T- and B- cell polarization by IVIg in a human-Dsg3-dependent mouse model for PV. Using humanized mice transgenic for HLA-DRB1*04:02, which is a highly prevalent haplotype in PV, we employed IVIg in two different experimental approaches: in prevention and quasi-therapeutic settings. Our data show that intraperitoneally applied IVIg was systemically distributed for up to 42 days or longer. IVIg-treated Dsg3-immunized mice exhibited, in contrast to Dsg3-immunized mice without IVIg, significantly less Dsg3-specific IgG, and showed induction of T regulatory cells in lymphatic tissue. Ex vivo splenocyte analysis upon Dsg3-specific stimulation revealed an initial, temporarily reduced antigen-induced cell proliferation, as well as IFN-γ secretion that became less apparent over the course of time. Marginal-zone B cells were initially reduced in the preventive approach but re-expanded over time. In contrast, in the quasi-therapeutic approach, a robust down-regulation in both spleen and lymph nodes was observed. We found a significant down-regulation of the immature transitional 1 (T1) B cells in IVIg-treated mice in the quasi-therapeutic approach, while T2 and T3, representing a healthy stage of B-cell development, appeared to be up-regulated by IVIg. In summary, in two experimental settings employing an active PV mouse model, we demonstrate distinct alterations of T- and B-cell populations upon IVIg treatment, compatible with a tolerance-associated polarization in lymphatic tissue. Our data suggest that the clinical efficacy of IVIg is at least modulated by distinct alterations of T- and B-cell populations compatible with a tolerance-associated polarization in lymphatic tissue.
Gesehen am 20.06.2023